MEMBACA(-ULANG) SEBUAH PUISI PAMPLET RENDRA: “SAJAK SEBATANG LISONG” - Kris Budiman (POETIKA, 2013)
The following essay is the result of  strict close reading of  a text poem, “Sajak Sebatang Lisong”, written by Rendra. Different with previous study about his poetry pamphlets, this essay will sit Renda on a more appropriateposition, that is a literary text –not as a social or historical document.Keywords: Rendra, poems, pamphlets, rereading